Peran Media Kotak Misteri dalam Meningkatkan Rasa Ingin Tahu dan Minat Belajar Siswa Sekolah Dasar - Anggraeni, Januar Winda; Rahmadhani, Eka Putri; Alfafa, Aura Jannatin; Oktavianti, Diana (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study used a systematic literature review (SLR) to analyze the use of mystery boxes in elementary school mathematics learning. The articles analyzed were selected based on inclusion criteria: they were published between 2020 and 2024 and discussed the application of mystery boxes in mathematics learning. The results showed that mystery boxes were effective in increasing students' curiosity and interest in learning. This media creates active, enjoyable, and interactive learning, thereby increasing students' enthusiasm and conceptual understanding. This study recommends mystery boxes as an alternative, innovative and effective learning medium for increasing elementary school students' interest in learning, particularly in mathematics. Therefore, mystery boxes can be a solution to address low student interest in learning and improve the quality of learning. This research can serve as a reference for teachers and researchers to develop more innovative and effective learning media. Mystery boxes have great potential to improve the quality of elementary school mathematics learning in a fun and interactive way.Penelitian ini menggunakan metode systematic literature review (SLR) untuk menganalisis penggunaan media kotak misteri dalam pembelajaran matematika di sekolah dasar. Artikel yang dianalisis dipilih berdasarkan kriteria inklusi, yaitu terbit pada tahun 2020–2024 dan membahas penerapan media kotak misteri dalam pembelajaran matematika. Hasil penelitian menunjukkan bahwa media kotak misteri efektif dalam meningkatkan rasa ingin tahu dan minat belajar siswa. Media ini menciptakan pembelajaran yang aktif, menyenangkan, dan interaktif, sehingga meningkatkan antusiasme dan pemahaman konsep siswa. Penelitian ini merekomendasikan media kotak misteri sebagai alternatif media pembelajaran inovatif dan efektif untuk meningkatkan minat belajar siswa sekolah dasar, khususnya dalam pembelajaran matematika. Dengan demikian, media kotak misteri dapat menjadi solusi untuk mengatasi rendahnya minat belajar siswa dan meningkatkan kualitas pembelajaran. Penelitian ini dapat menjadi referensi bagi guru dan peneliti untuk mengembangkan media pembelajaran yang lebih inovatif dan efektif. Media kotak misteri sangat berpotensi untuk meningkatkan kualitas pembelajaran matematika di sekolah dasar dengan cara yang menyenangkan dan interaktif.